Case Report: Novel Mutation of F5 With Maternal Uniparental Disomy Causes Severe Congenital Factor V Deficiency - Cheng, Lin; Li, Ying; Zhou, Wenjuan; Bo, Tao (Frontiers in Pediatrics, 2022)
We summarized case 1 and the mother of case 1 with congenital factor V deficiency (FVD) associated a novel F5 mutation, and analyzed the relationship of the clinical features and genetic characteristics in congenital FVD. Case 1 was the female newborn infant with remarkable bleeding and died of severe intracranial hemorrhage on day 42 after birth. She had significant prolongation of prothrombin time (PT) and activated partial thromboplastin time (APTT). Percentage activity of FV (PFV) was lower than 3% in case 1. The mother of case 1, who showed no tendency to bleed. She was mild prolongation of PT and APTT. PFV was only 43%. Both cases were identified the same novel mutation in F5, which was c.5419G>A (p.Ala1807Thr) in exon16. The variant in case 1 was inherited from the mother of case 1. Whole-exome sequencing (WES) also found a splice site mutation, 103Mb maternal uniparental disomy (UPD) of 1q21.1-qter in case 1, F5 gene is located in the segment. So case 1 was homozygote and the mother of case 1 was heterozygote. The novel mutation of F5 was predicted harmful by bioinformatics softwares including Sorting Intolerant From Tolerant (SIFT), Polyphen2, LRT, Mutation Taster. In summary, c.5419G>A (p.Ala1807Thr) in exon 16 of F5 is a pathogenic mutation, which causes severe congenital FVD in homozygote.